Fractional Moisil-Teodorescu operator in elasticity and electromagnetism - Juan Bory-Reyes; Marco Antonio Pérez-de la Rosa; Yudier Peña-Pérez (Alexandria Engineering Journal, 2022)
In this work, we introduce a fractional generalization of the classical Moisil-Teodorescu operator that provides a concise notation for presenting a mathematical formulation of physical systems in fractional space from various branches of science and engineering. The method used in this article, called the Stillinger’s formalism, is combined in a novel way with quaternionic analysis. As a concrete application, a quaternionic reformulation of a fractional time-harmonic Maxwell system is established, thus showing a deep relation between it solutions with those of the perturbed fractional Moisil-Teodorescu operator. Furthermore, the fractional constructions here will find further applications in several applied research areas such as in hydrodynamics and magneto-hydrodynamics.